Use of NDVI for characterizing winter wheat response to water stress in a semi-arid environment. Issue 5 (3rd September 2019) - Thapa, Sushil; Rudd, Jackie C.; Xue, Qingwu; Bhandari, Mahendra; Reddy, Srirama K.; Jessup, Kirk E.; Liu, Shuyu; Devkota, Ravindra N.; Baker, Jason; Baker, Shannon
ABSTRACT: The normalized difference vegetation index (NDVI) has been widely used to quantify vegetation by measuring the difference between near-infrared (NIR) and red light. Measuring NDVI throughout a growing season helps to evaluate the effect of continuous phenological and morphological changes on grain yield. A 2-year field study was conducted to characterize plant response to water stress in 20 winter wheat ( Triticum aestium L.) genotypes during the season based on their NDVI values under the dryland and irrigated conditions. In addition, final biomass and yield were measured at maturity. The 2018 season was extremely dry with only 23 mm of precipitation, whereas 2016 was more favorable for wheat production with 315 mm seasonal precipitation. Except in a severe drought condition (2018, dryland), NDVI values increased from early spring to mid-season (anthesis) and decreased from mid-season to physiological maturity, indicating gradual leaf senescence. There was a significant (P = 0.05) positive correlation between NDVI and grain yield, especially for NDVI values after jointing. However, under the severe drought condition of 2018 (dryland), NDVI often did not show a strong relationship with grain yield. Even genotypes with higher NDVI at early growth stages ended up with lower yield because of the severe water stress at later growth stages. Hence, the use of NDVI is not suggested in screening genotypes for yield under extreme weather conditions.